(untitled) (Journal of Enam Medical College, 2018)
Background: Dermatophytosis is considered as one of the major public health problems in the world and is the most commonly diagnosed skin disease in Bangladesh. The prevalence and characteristics of dermatophytic infections vary with climatic conditions, age, lifestyle and population migration patterns. Objective: To determine the prevalence of dermatophytic infection and sensitivity of different diagnostic procedures among the patients visiting dermatology outpatient department of Tairunnessa Memorial Medical College & Hospital, Gazipur, Bangladesh (TMMCH). Materials and Methods: This cross-sectional study was done during a period of 12 months from July 2015 to June 2016. Total 80 specimens were collected based on clinical presentations irrespective of age and sex. The diagnosis was confirmed by microscopic examination using 20% potassium hydroxide (KOH) and culture on Sabouraud’s dextrose agor medium. Results: Out of 80 samples, 31(38.75%) were found positive by culture and 21 (26.25%) were found positive by microscopic method which were also found positive by culture. This study found that most (51.62%) of the dermatophyteinfected cases were in the age group of 21−40 years followed by 41−60 years (29.03%) with male and female distribution 58.06% and 41.94% respectively The maximum number of infections was reported from groin followed by hands/legs and feet. Conclusion: The result of this study shows higher prevalence of dermatophytosis in both genders in this area. An accurate diagnosis can help in proper and effective treatment of dermatophytosis. J Enam Med Col 2018; 8(1): 11-15